Pemadam Kebakaran dan Artifical Intelligence (AI): : Inovasi atau Substitusi? - Akira Riofuku (Gerakan Indonesia Kita, 2025)
The firefighting profession has increasingly become a subject of public attention, not only due to its critical role in fire suppression but also because of its expanding responsibilities in various non-fire emergencies. Simultaneously, the rapid advancement of Artificial Intelligence (AI) has sparked debates regarding its potential to replace human roles, particularly in public safety services. AI is often praised for its speed, accuracy, and efficiency in tasks such as early fire detection, real-time situational mapping, and autonomous system operations. This paper aims to examine whether AI can fully substitute the human role in firefighting or whether it is better positioned as a technological tool that enhances human capability. Employing a qualitative methodology based on literature review and philosophical reflection—including perspectives from Sartrean existentialism, Merleau-Ponty’s phenomenology, Heidegger’s philosophy of technology, and Kantian ethics—this study argues that while AI offers innovative support, it cannot replace the existential, moral, and embodied dimensions inherent in the firefighter’s profession.